Sistem Pemantauan Panel Listrik 3 Fasa Untuk Pengukuran Energi Listrik Berbasis ESP32 - Sobri Rizaldi Subroto; Aditya Chandra Hermawan; Mahendra Widyartono; Fithrotul Irda Amaliah; Ayusta Lukita Wardani (Politeknik Negeri Malang, 2026)
Electricity consumption continues to increase as electronic equipment is used, resulting in rising monthly electricity bills. The background to this title stems from an electricity consumption survey. The survey team encountered difficulties monitoring electricity usage on the electrical panels in each building. The urgency of this research is to facilitate monitoring of electricity usage on three-phase electrical panels that can be easily installed and removed for use in various electrical panels The electrical energy data is accumulated from all three phases every second to determine the total electrical energy consumption across all three phases, the ESP32 microcontroller is also used as the brain for controlling the transmission and recording data in a Google spreadsheet for data storage.The results of the electrical energy measurement test, comparing the designed device with 3-phase kWh meter over six days of testing, revealed that the error value of the designed device was 0.26%, which is the maximum error value stipulated error limit of ±1%. This indicates that the designed measuring instrument has a high level of accuracy and meets international measuring instrument standards, with an average accuracy of 99.74%. The IEC 62053-21 standard is an international reference standard that regulates the accuracy and error limits for electrical energy meters (kWh meters). These results indicate that the designed electrical energy monitoring device is capable of performing well and accurately, approaching the values ​​of standard electrical energy meters (kWh meters).